The association between obesity and migraine and possible mechanisms of action: an integrative literature review - Halaiko, Dieniffer Aparecida; Faro, Paulo; Levis, Aline Andretta; Netto, Bárbara Dal Molin (Headache Medicine, 2021)
Introduction Obesity is a multifactorial disease and is defined by the excessive accumulation of adipose tissue that can cause harm to human health. The presence of obesity is an important risk factor for migraine chronification. However, not much is known about the link between the two diseases. Methods In this study, an integrative literature review was conducted to better understand the mechanisms of interaction between migraine and obesity. Therefore, a search of PubMed and the Virtual Health Library (VHL) was performed with the following keywords: enxaqueca e obesidade; enxaqueca e obesidade e inflamação; enxaqueca e obesidade e neuropeptídeos; migraine and obesity; migraine and obesity and inflammation; migraine and obesity and neuropeptides. Results The search identified 22 articles. After reading and analyzing the articles, three thematic categories emerged: 1) Obesity as an Aggravating Factor for Migraine 2) Mechanisms Studied between Obesity and Migraine 3) The Effect of Weight Loss on Migraine Symptoms. Conclusions The chronic low-grade inflammation associated with obesity can cause a predisposition to migraine chronification. The abnormal secretion of adipokines, dysregulation of the sympathetic nervous system, and hypothalamic dysfunction have been suggested to be the main shared mechanisms between both diseases.